2021
DOI: 10.1002/anie.202114080
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Plane is not the Key Factor for CO2‐to‐Methane Electrosynthesis on Reconstructed Cu2O Microparticles

Abstract: Cu 2 O microparticles with controllable crystal planes and relatively high stability have been recognized as a good platform to understand the mechanism of the electrocatalytic CO 2 reduction reaction (CO 2 RR). Herein, we demonstrate that the in situ generated Cu 2 O/Cu interface plays a key role in determining the selectivity of methane formation, rather than the initial crystal plane of the reconstructed Cu 2 O microparticles. Experimental results indicate that the methane evolution is dominated on all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 73 publications
0
57
0
Order By: Relevance
“…Mechanism studies by in-situ ATR-SEIRS and DFT calculations. To understand the improved CO 2 R activity of the CuI-CO 2 nanodots for C 2 H 4 generation, we performed in-situ electrochemical attenuated total re ection surface-enhanced Fourier-transform infrared spectroscopy (ATR-SEIRS) analysis [36][37][38][39] (Fig. 6) and DFT calculations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism studies by in-situ ATR-SEIRS and DFT calculations. To understand the improved CO 2 R activity of the CuI-CO 2 nanodots for C 2 H 4 generation, we performed in-situ electrochemical attenuated total re ection surface-enhanced Fourier-transform infrared spectroscopy (ATR-SEIRS) analysis [36][37][38][39] (Fig. 6) and DFT calculations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 uncover the adsorption of intermediates for C 2 H 4 formation over CuI-CO 2 , CuI-N 2 and Cu-CO 2 electrocatalysts. Along with negatively scanning potentials from open circuit potential (OCP) to -1.1 V vs RHE, a weak peak at 2036 cm − 1 corresponding to adsorbed CO (*CO) 36,38,39 becomes visible and then gradually disappears, accompanied by the progressive emergence of new peaks assignable to reduced *CO for the CuI-CO 2 (Fig. 6a), suggesting the effective adsorption of *CO intermediates and their rapid reductive conversion.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Deng and co-workers revealed that the Cu 2 O/Cu interface can contribute to the selectivity of CH 4 . [11] Moreover, Li et al synthesized nitrogen-doped carbon-coated Cu and demonstrated that Cu/N x C interface boosted the formation of C2 products. [12] However, their partial current density is generally very low (generally lower than −300 mA cm -2 ), which is difficult to meet the needs of industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, their partial current density is generally very low (generally lower than −300 mA cm -2 ), which is difficult to meet the needs of industrialization. [10][11][12] Thus, the combination of tunable valence state (Cu 0 /Cu 2+ /Cu + ) and structure are necessary for Cu-based catalysts to achieve high activity and selectivity for CO 2 RR. [13] Metal-organic framework (MOFs) materials with porous structures enable more active sites, which are promising candidates for efficient CO 2 activation and electron transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation